2010
DOI: 10.1016/j.jacc.2010.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Human Peripheral Blood-Derived CD31+Cells Have Robust Angiogenic and Vasculogenic Properties and Are Effective for Treating Ischemic Vascular Disease

Abstract: Objectives This study aimed to determine if CD31 is a novel marker of a circulating angio-vasculogenic cell population and to establish their therapeutic effects on experimental ischemia. Background Emerging evidence suggested that therapeutic mechanisms underlying various bone marrow (BM)-derived cells are due to paracrine effects. Furthermore, the vasculogenic potential of these cells is under debate. CD31 is a well known marker for endothelial cells (ECs) but is also expressed in a fraction of peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(144 citation statements)
references
References 29 publications
5
136
0
3
Order By: Relevance
“…By one week post-treatment, animals that received matrix treatment (with or without SDF-1 microspheres) had hindlimb perfusion restored to baseline levels, which is similar to previous reports of matrix treatment for hindlimb ischaemia . It has been previously demonstrated that an increase in perfusion is attributable to increased local vasculature (Kim et al, 2010;Suuronen et al, 2010), an observation that was seen in the current study; matrix treatments increased arteriole density in ischaemic hindlimbs. It was hypothesised that SDF-1 microsphere matrix treatment would confer superior restoration of perfusion, but instead, the matrix-only treatment was equally effective.…”
Section: Kuraitis Et Al Controlled Sdf-1 Release For Treating Ischsupporting
confidence: 82%
“…By one week post-treatment, animals that received matrix treatment (with or without SDF-1 microspheres) had hindlimb perfusion restored to baseline levels, which is similar to previous reports of matrix treatment for hindlimb ischaemia . It has been previously demonstrated that an increase in perfusion is attributable to increased local vasculature (Kim et al, 2010;Suuronen et al, 2010), an observation that was seen in the current study; matrix treatments increased arteriole density in ischaemic hindlimbs. It was hypothesised that SDF-1 microsphere matrix treatment would confer superior restoration of perfusion, but instead, the matrix-only treatment was equally effective.…”
Section: Kuraitis Et Al Controlled Sdf-1 Release For Treating Ischsupporting
confidence: 82%
“…Animal experiments were performed as described previously. 12 Mice were anesthetized with isoflurane (induction: 450 ml air, 4.5% isoflurane; maintenance: 200 ml air, 2.0% isoflurane; Baxter International, Inc, Deerfield, IL, USA), and the depth of anesthesia was monitored by respiratory rate and lack of withdrawal reflex upon toe pinching. 4 Hindlimb ischemia was induced by ligation of the right femoral artery.…”
Section: Transplantation Of Cells In the Ischemic Hindlimb Animal Modelmentioning
confidence: 99%
“…21 --23 Therefore, we generated ischemic hindlimbs by unilateral femoral artery ligation, as previously described, 24,25 and then injected them with CVB3 --FGF2, CVB3 --GFP, CVB3 or PBS. CVB3 --FGF2 significantly protected the hindlimbs from ischemic necrosis compared with PBS, CVB3 and CVB3 --GFP in BALB/c mice (Po0.05; Figure 4), whereas there were no differences in limb salvage among the PBS, CVB3 and CVB3 --GFP groups, which all showed significant limb necrosis (Figure 4).…”
Section: Cvb3 --Fgf2 Protects Against Ischemic Necrosis and Improvesmentioning
confidence: 99%